HIV surveillance : a 12 year analysis of HIV prevalence trends and comparing HIV prevalence from sentinel antenatal clinic surveys and prevention of mother-to-child programmes - Essel, Vivien (Department of Public Health and Family Medicine, 2015)
Background Sentinel antenatal clinic (ANC) surveys remain a key source of data on HIV prevalence trends. Recently though, with an increase in the uptake of prevention of mother-to-child transmission (PMTCT) programmes, there have been debates on the prospects of using PMTCT data for reporting antenatal HIV prevalence and trends. Aim To describe the HIV prevalence trends for the Western Cape Province and to compare prevalence from ANC surveys to PMTCT programmes. Methods HIV prevalence and 95% confidence intervals were estimated from ANC surveys from 2001-2012 for the province as well as the 6 health districts and the 8 City of Cape Town Metropolitan sub-districts in the province. HIV prevalence from expanded provincial ANC survey sampling was compared to the nationally reported provincial and district estimates, before and after re-weighting to account for differences between the realized sample and updated sampling frame. A regression line was fitted with calendar year included as both a linear and quadratic term to create smoothed trend lines of the change in HIV prevalence over time by province, district, sub-district and age group. A multivariable logistic regression model was fitted to the multi-year ANC survey data to explore associations with HIV prevalence. ANC survey HIV prevalence estimates were compared to those from routinely reported HIV testing data from the PMTCT program for 2009-2012.